Forces achieved by different material and type of intrusion arches applied in different horizontal levels - Kılınç, Delal Dara (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Intrusion is one of the most needed movements in orthodontics. It is possible to achieve this with arch wires, miniscrews, and bite-blocks. Purpose: This in vitro study aimed to evaluate forces achieved by different types of intrusion arches made of different materials and anchored in two different horizontal levels by either miniscrews or molar teeth. Methods: An upper jaw typodont was applied different types of intrusion arches: intrusion and utility arches, made of different materials (nitinol, beta III titanium, stainless steel) and different wire sizes (0.016” x 0.022” and 0.017” x 0.025”) to the incisors, both anchoring from molars and miniscrews respectively. Each application was measured by a Correx gauge. Each wire was applied to both the auxiliary slot of the triple tube and the slot in the head of the miniscrew. One-way analysis of variance (ANOVA), Tukey's HSD test, and a paired two-sample t-test were used to analyze the data. Results: In the intrusion arches, the main effect of the material was found to be statistically significant on force values (p = 0.034) while the main effect of the size was not found statistically significant on force values (p = 0.083). In the utility arches, both the main effect of the material (p = 0.067) and the size (p = 0.140) were not found to be statistically significant on force values. Conclusion: Regardless of the anchorage unit level and size, nitinol was the material that applied the lowest forces among all materials. The material is the most effective factor in the force generated, while the anchorage unit level is the least.